Biodiversity of tiger beetles from Angola with the description of a new species of the genus Neochila Basilewsky, 1953 (Coleoptera: Cicindelidae) - Serrano, Artur R. M.; Capela, Rúben A.; Santos, Carmen Van-Dúnem (Zootaxa, 2019)
One new tiger beetle species of the genus Neochila Basilewsky, 1953 is described from Angola. The genus is a new record for this country also. An annotated list of species of Cicindelidae sampled in Angola, including data on distribution and general ecology of these beetles is presented. Further, a dichotomic key is made available for the identification of Neochila species of the katangana group.